1991
DOI: 10.1099/0022-1317-72-1-75
|View full text |Cite
|
Sign up to set email alerts
|

Deduced Amino Acid Sequence of the Fusion Glycoprotein of Turkey Rhinotracheitis Virus has Greater Identity with that of Human Respiratory Syncytial Virus, a Pneumovirus, than that of Paramyxoviruses and Morbilliviruses

Abstract: The sequence of the fusion (F) glycoprotein of turkey rhinotracheitis virus (TRTV) has been deduced from cDNA clones derived from oligo(dT)-selected infected cell RNA. The protein consists of 538 amino acids, the F2 and F1 subunits containing 102 (including the F2-F1 connecting peptide RRRR) and 436 residues, respectively. Each subunit has one potential N-linked glycosylation site. The protein has 38 to 39% amino acid identity with the F protein of respiratory syncytial virus (Pneumovirus genus) but only about… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 35 publications
1
44
0
Order By: Relevance
“…matrix (M) proteins of TRTV (Yu et al, 1991(Yu et al, , 1992 mostly closely resemble the analogous proteins of human respiratory syncytial (RS) virus, the pneumovirus that has been studied in greatest detail (for a review, see Collins, 1991). Interestingly, however, we have found a difference in gene order between TRTV and the mammalian pneumoviruses, which also include bovine RS virus and pneumonia virus of mice (PVM; Chambers et al, 1990).…”
Section: Introductionmentioning
confidence: 71%
See 2 more Smart Citations
“…matrix (M) proteins of TRTV (Yu et al, 1991(Yu et al, , 1992 mostly closely resemble the analogous proteins of human respiratory syncytial (RS) virus, the pneumovirus that has been studied in greatest detail (for a review, see Collins, 1991). Interestingly, however, we have found a difference in gene order between TRTV and the mammalian pneumoviruses, which also include bovine RS virus and pneumonia virus of mice (PVM; Chambers et al, 1990).…”
Section: Introductionmentioning
confidence: 71%
“…The TRTV strain used was UK/3BV/85 and this was propagated in Vero cells (Yu et al, 1991). The coronavirus infectious bronchitis virus (IBV) was also propagated in Vero cells.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consensus predictions were obtained simply by averaging the scores of the individual sequences of the F proteins of the pneumoviruses PVM, HRSV (Collins et al, 1984) and TRTV (Yu et al, 1991), and the paramyxoviruses NDV (Chambers et al, 1986), Sendal virus (Shioda et aL, 1986) and simian virus 5 (SV5) (Paterson et al, 1984), which closely resemble each other (not shown) and the average predictions. Only the extracellular parts of the F protein were considered, and positions where gaps in the alignment (taken from Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The first APV gene to be cloned and sequenced was that of the fusion (F) protein gene of a subtype A virus (Yu et al, 1991), since when all the other genes of a subtype A virus have been sequenced (Ling et al, 1992;Yu et al, 1992a,b;Ling et al, 1995;Li et al, 1996;Randhawa et al, 1996bRandhawa et al, , 1997. Fewer genes of subtype B virus have been sequenced: G protein (Juhasz & Easton, 1994), M protein (Randhawa et al, 1996a) and N protein (Li et al, 1996).…”
Section: Sequence Data For the Avian Pneumovirusesmentioning
confidence: 99%